Analysis of Indonesia’s Car Exports During Vehicle Electrification in Export Destination Countries 2016-2022 - Naufal, Muhammad; Artiani, Listya Endang (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The concern for low-emission economic activities has made many countries electrify vehicles as a step to reduce CO2 emissions. The share of electric vehicle (EV) sales in the world continues to increase exponentially, accompanied by a decrease in the average price of EVs in the world. This is feared to threaten Indonesia's car exports, which are dominated by the internal combustion engine (ICE) type. This study aims to analyze the competitive advantage position of Indonesia's car exports as well as the factors affecting Indonesia's car exports in the country with the largest EV share. The research methods used are export products dynamics (EPD) analysis and unbalanced panel regression analysis. The independent variables used are Indonesia's car export prices, GDP per capita of destination countries, average EV prices of destination countries, revealed comparative advantages (RCA) values, and dummy free trade agreements (FTAs). The dependent variable used is the export value of Indonesia's cars with HS code 8703. The results of the study using EPD show that most of Indonesia's car exports in destination countries are in a less expected position, namely falling stars. The results of the regression analysis show that car export prices and EV prices in destination countries have a significant negative effect. GDP per capita and RCA have a significant positive effect, while FTA has no effect.